Correction: Gut microbiome modifications over time when removing in-feed antibiotics from the prophylaxis of post-weaning diarrhea in piglets. - Paola Cremonesi; Filippo Biscarini; Bianca Castiglioni; Carlo Angelo Sgoifo; Riccardo Compiani; Paolo Moroni (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0262199.].